2019
DOI: 10.3389/fgene.2019.00711
|View full text |Cite
|
Sign up to set email alerts
|

Wnt, Notch, and TGF-β Pathways Impinge on Hedgehog Signaling Complexity: An Open Window on Cancer

Abstract: Constitutive activation of the Hedgehog (Hh) signaling pathway is associated with increased risk of developing several malignancies. The biological and pathogenic importance of Hh signaling emphasizes the need to control its action tightly, both physiologically and therapeutically. Evidence of crosstalk between Hh and other signaling pathways is reported in many tumor types. Here, we provide an overview of the current knowledge about the communication between Hh and major signaling pathways, such as Notch, Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 236 publications
(256 reference statements)
1
72
0
1
Order By: Relevance
“…Dysregulation of Hh signaling has been implicated in several cancers including esophageal [67], gastric [68], pancreatic [69], as well as liver [70]. Previous studies showed activated Hh signaling may attenuate Wnt activity through the high expression of the Wnt inhibitor, SFRP1 [63,71,72].…”
Section: Involvement Of Sfrp1 In the Hedgehog Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of Hh signaling has been implicated in several cancers including esophageal [67], gastric [68], pancreatic [69], as well as liver [70]. Previous studies showed activated Hh signaling may attenuate Wnt activity through the high expression of the Wnt inhibitor, SFRP1 [63,71,72].…”
Section: Involvement Of Sfrp1 In the Hedgehog Signaling Pathwaymentioning
confidence: 99%
“…Hh pathway activation is achieved by the interaction of Hh ligands to the Patched receptor (Ptch), and thus allows the accumulation of the transducer smoothened (SMO) at the cell surface. The accumulated SMO stimulates downstream components of the signaling pathway including Gli1 molecules, which then translocate into the nucleus and further activate the Hh target genes [72,73]. SFRP1 is a Hh target gene and is significantly regulated by Gli1 [71].…”
Section: Involvement Of Sfrp1 In the Hedgehog Signaling Pathwaymentioning
confidence: 99%
“…Few pathway analyses have shown that, Molecular signaling such as beta pathway on hedgehog signaling may lead to tumorigenesis [25,26]. PI3K/AKT/mTOR signaling pathways and NKX6, a transcription factor for Wnt/β-catenin and Rho-GTPase signaling-related genes play key role for carcinogenesis [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular signaling pathways, such as Wnt (WNT) and Notch Signaling pathways (NOTCH a highly conserved cell signaling system, 4 different receptors i.e. NOTCH 1,2,3 and 4), Sonic hedgehog (SHH signaling is intricate signal transduction), and MYC for apoptosis and cellular transformation play critical role in the pathogenesis of GC[25]. Nuclear factor-kB (NF-kB), epidermal growth factor receptor (EGR)[26] and some epigenetic alterations such as DNA methylation, histone modifications, histone acetylation and histone phosphorylation observed in all type of Cancers.…”
mentioning
confidence: 99%
“…Highly advantageous effects have been observed after losartan treatment [121,123], and in addition, this drug is considered safe, it is relatively inexpensive, and it is already widely prescribed as an antihypertensive agent [147,148]. In contrast, routine clinical use of treatments targeting the Hh pathway lies further up the road, as inhibition of Hh signaling has provided conflicting findings both in animal models and patients, despite it being crosstalk between the TGF-β and Hh pathways in cancerous tissue [118,149]. Also therapeutic strategies aiming to degrade and/or destabilize the ECM directly as well as treatments targeting CAFs, such as ATRA treatment, have to be investigated further before their clinical potential can be assessed.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%